ANALYSIS OF CHANGES IN AUTO REJECTION REGULATIONS DUE TO THE COVID-19 PANDEMIC AND ITS EFFECT ON THE INDONESIA SHARIA STOCKS INDEX - Bagas Heradhyaksa (Journal of Islamic Studies and Humanities, 2022)
The number of Single Identity Investors in Indonesia continues to increase. This shows that the Indonesian people are increasingly understanding investment. The most popular form of investment in society is stock investment. Shares that have been adjusted to the principles of Islamic law are sharia shares. The price movement of sharia shares can be known through the sharia stock index. Stock prices, both conventional and Islamic stocks, have experienced very volatile movements due to the COVID-19 pandemic. Therefore, the Indonesia Stock Exchange made changes to the Auto Rejection regulation. Auto rejection is a scheme in the Indonesian stock exchange to automatically reject the offer to sell and/or request to buy securities. This article aims to find out how changes in auto rejection regulations affect the sharia stock index. Data from literature references and official websites were analyzed using qualitative methods. The results are presented in an analytical descriptive manner. From the analysis process, it is known that there is an increase in the percentage of the minimum limit for auto rejection. This results in stricter auto rejection. This change is intended so that the price movement of a stock is not too volatile even though it is in a state of the COVID-19 pandemic.